2017
DOI: 10.1007/s11356-017-0406-3
|View full text |Cite
|
Sign up to set email alerts
|

Micro-pollutants in sediment samples in the middle Danube region, Serbia: occurrence and risk assessment

Abstract: This is the first comprehensive study on the occurrence of 940 semi-volatile organic compounds including sterols, polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), pesticides, plasticizers, and other emerging compounds in 10 river and canal sediments collected in northern Serbia. For quantification of investigated compounds GC-MS-MS (selected reaction monitoring) and GC-MS (using both selected ion monitoring and total ion monitoring) methods were used. The number of detected compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…HCH’s concentration in the Awash River basin was similar to its concentrations in the Soan River, Pakistan [ 43 ]. A wide range of concentrations of HCH was recorded in this study as compared to report on the surface sediments of the Rivers in middle Denube, Serbia [ 44 ] and the Yellow River, China [ 45 ]. In contrast, the range of HCH concentration in this study area was found to be lower than a report from the Qiantang River, China [ 15 ].…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…HCH’s concentration in the Awash River basin was similar to its concentrations in the Soan River, Pakistan [ 43 ]. A wide range of concentrations of HCH was recorded in this study as compared to report on the surface sediments of the Rivers in middle Denube, Serbia [ 44 ] and the Yellow River, China [ 45 ]. In contrast, the range of HCH concentration in this study area was found to be lower than a report from the Qiantang River, China [ 15 ].…”
Section: Resultsmentioning
confidence: 54%
“…The concentration of ∑DDTs was lower than reports in the Qiantang River, China [ 15 ], the Rivers in middle Denube, Serbia [ 44 ] and on the Soan River, Pakistan [ 43 ]. Whereas higher concentration of ∑DDT was recorded in this study area as compared to reports on the Huaihe River, China [ 46 ].…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…No comparisons can be made neither for the values of Σ16PAHs or Σ6PCBs in Danube River sediment. Škrbić 's et al study reported values includes tributary, where larger amounts of pollutants are usually found [95], while Radu's et al study does not [84]. In terms of PCBs, Brborić et al reported the sum of seven PCB congeners [94] while Radu et al reported only 6six of them [84].…”
Section: Persistent Organic Pollutantsmentioning
confidence: 94%
“…The pollution of the second longest European river (the River Danube) has been under monitoring and focused on emerging contaminants including metals/metalloids (Hg, As, Ni, Zn, Cu, Cr, Pb, and Cd), personal care products, technical additives, pesticides, pharmaceuticals, steroids, and perfluorinated compounds (Milenković et al 2005 ; Škrbić et al 2018 ; Vuković et al 2012 ; Ivanović et al 2016 ; Comero et al 2014 ; Reschke et al 2002 ; Matić Bujagić et al 2019 ). The biggest hydropower dam and reservoir system along the Danube River is Iron Gate I on Đerdap Gorge, 117 km long.…”
Section: Introductionmentioning
confidence: 99%